Anatomia da madeira, incremento radial, fenologia e relações hídricas em ecótipos de Plathymenia reticulata Benth. (Leguminosae, Mimosoideae) - Marcos Miranda Toledo (2010)
Plathymenia Benth. (Leguminosae, Mimosoidae) is a widely distributed genus across the Neotropical Savanna and Atlantic Forest biomes, with a long history of taxonomic controversies. The forest species, P. foliolosa, was recently proposed as a synonym of the savanna species, P. reticulata. Ecophysiological and genetic studies both revealedpopulations adapted to these biomes, supporting the existence of two ecotypes, rather than two species. Despite the economic importance of its wood, little is known about the cambial activity and xylem structure of P. reticulata. This study aims to analyze possible differences between the ecotypes regarding xylem physical and anatomical traits (and physiological consequences arising from them); and investigatesdifferences in cambial activity, linking it to phenology, water status andenvironmental variables. Fourteen individuals from each P. reticulata ecotype were selected in a forest-savanna boundary in Southeastern Brazil and radial increment, phenology and water status were monthly assessed. Wood physical and anatomical analyses were also carried out. Univariate and multivariate analyses were carried out with the data. The Forest ecotype individuals had lower wood density and consequently higher saturation water content, which means higher capacitance. Largervessels, although in lower frequency, resulted in higher potential hydraulic conductivity of the Forest ecotype compared to the Savanna ecotype. However, the Savanna ecotype had a potentially higher resistance to embolism. Wood density and individual size were the best predictors for separating the ecotypes. However, the individuals were sparsely distributed throughout ordination axis 2, which was relatedto vessel traits. Spearman correlation shows wood density as the most strongly correlated variable. The variation in stem diameter was due to irreversible growth by cambial activity, and either tissue hydration or dehydration. Monthly precipitation and deciduousness were strongly correlated to cambial activity. The Forest ecotype showed greater variation in diameter and greater final increment, which is consistent with tissues traits. Water status was not correlated with radial increment, but wasinfluenced by phenology. Leaf-fall contributed to high water potential values during the dry season, which allows leaf flushing to occur before the first rains. The higher capacitance determined by lower wood density allowed the Forest ecotype to compensate the water lost by leaves with less reduction in water potential. We 4 conclude that ecotypes, even under similar climatic conditions, show distinct morphofunctional wood traits and radial growth. The presence of ecotypes with anatomical, functional and physiological differences in the transitional region is anadvantage for the survival of P. reticulata as it may enable a variety of populationlevel responses to climate changes, reflecting in the current and future distribution of the species.